Assessment of the efficiency of cognitive function of people over 65 - Tomaszewska, Katarzyna; Majchrowicz, Bożena; Kłos, Alicja (Journal of Education, Health and Sport, 2018)
Demographic estimates for Poland indicate that the average life expectancy of the population will increase further over the next decades. Weakness of memory is a physiological phenomenon affecting about 60% of people over 65, whereas the prevalence of dementia in the population is estimated at 10-11%. Identification of people at high risk of developing dementia is becoming a significant medical and social problem. Cognitive impairment is one of the first symptoms of dementia. The Mini-Mental State Examination (MMSE) is a screening method that allows initial assessment of cognitive performance. Correct diagnosis of symptoms, determining the health needs of seniors in all dimensions sets its further paths and optimal medical treatment.Aim of the paper: The aim of this paper is to assess the efficiency of cognitive function of people over 65.Material and methods: The analysis included 135 questionnaires of the Mini-Mental State Examination (MMSE) and respondents’ particulars. Additionally, the functional efficiency of the subjects was assessed using the Barthel scale. The research was conducted among people over 65 in the Podkarpackie Voivodeship in 2017. For the purpose of this work, especially for verification of hypotheses, the following tests were used for questions on nominal scales: V Kramer (2x3, 4x5 tables etc.), Phi (2x2 tables). Tb-Kendall or Tc tests were used for questions on ordinal scales. The statistical analysis was carried out using the SPSS program and all relationships were statistically significant when p <0.05.Results and conclusions: The number of co-occurring chronic diseases increases with age. In the study population of people over 65, the percentage of responders with mild cognitive impairment according to the MMSE score was 12.4%. The problem of dementia of a significant severity according to this scale concerned 26.1% of respondents. Sex of the subjects did not have a statistically significant effect on the degree of development of dementia. There is a weak statistically significant correlation, which informs that the older patients are, the more often they have a higher degree of dementia. Moreover, the higher the level of education respondents have, the more often they are characterized by a lower level of dementia.